4y-13=

Simple and best practice solution for 4y-13= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-13= equation:


Simplifying
4y + -13 = 0

Reorder the terms:
-13 + 4y = 0

Solving
-13 + 4y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 4y = 0 + 13

Combine like terms: -13 + 13 = 0
0 + 4y = 0 + 13
4y = 0 + 13

Combine like terms: 0 + 13 = 13
4y = 13

Divide each side by '4'.
y = 3.25

Simplifying
y = 3.25

See similar equations:

| 4y+38=20+8y | | 2(x+15)=x+21 | | y(49/60)=(7/2) | | x+15=x+21 | | =ln(0.5x^2) | | ((x^2)+y)dx=-xdy | | 6(2n-2)=(8n+8)+1 | | a=1/2bc2 | | (5x-14)+90+y=180 | | 3n-1=-28 | | 4a+8=2a | | 5m-1=14 | | 5L-12=38 | | (2x+13)+3x+57=180 | | -k+5=24 | | -8j-59=13 | | 5*x+57= | | 14i-5=-33 | | 14I-5=-93 | | 3(x-2)+2x=7-(x+5) | | (2c-3)(2c+4)(2c-1)=0 | | 70=(x*x+2*2) | | -12g-4=44 | | -10m+8=-8 | | (x^2+9x+4)=0 | | 6(x-5)=50-4x | | 19f+36=112 | | 5m+7m=17 | | 11e-4=-48 | | X+9y=89 | | 11e-4=44 | | 9d-30=15 |

Equations solver categories